The way you hold me - Wright, Elle (Wright, Elle. Pure Talent series., 2020)
"Skye Palmer puts out the biggest publicity fires for Pure Talent's top names. But when an A-list Hollywood actress' dream marriage proves anything but, Skye has to do nightmare damage control. Even worse, her ex-lover, attorney Garrett Steele, is crisis manager for her client's powerful director husband. Now for Skye and Garrett, containing this disaster--and keeping their reignited passion in check--may be mission impossible..."--